(untitled) (Scientific journal of the Fergana State University, 2026)
The article goals to substantiate that the tradition of creating poems based on the synthesis of plots and motifs of folk epics continues in the Uzbek poetry of the independence period, and that this tradition, meeting the aesthetic needs of the literature of that period, is becoming more active in the works of the creators of that period and serves the ideological goal of the poet. To achieve this goal, the article analyzes poems created under the influence of episodes and motifs of folk epics in the Uzbek poetry of the independence period, using semiotic, structural, hermeneutic methods, as a result of which aspects of the manifestation of the synthesis of folk epics and poetry are revealed, and the following conclusions are drawn: In Uzbek poetry of the independence period, poets achieve their ideological and aesthetic goals by synthesizing various components of folk epics with poetry: imagery, plot, motifs, and modes of expression. In the poetry of this period, the development of lyrical plot takes a leading role, conveying the image of lyrical experience through the use of imagery, plots, and motifs from folk epics, either unchanged or based on paradoxical approaches and modifications. Poets such as Usman Azim, Rauf Subhon, Sukhrab Ziyo, Najmiddin Ermatov, Abdunabi Hamro, and Nozima Khabibullayeva develop lyrical plots based on episodes and motifs from folk epics. They express lyrical experiences using figurative devices like talmeh and allusion, referencing events from folk epics and contemporary realities. These poets synthesize components of folk epics into their poems, employing fragments and expressive methods characteristic of folk epics as a form of analytical folklorism; they creatively use this tradition, which meets the aesthetic needs of the literature of that period, to illuminate various social problems and issues related to the fate of the country in the artistic thinking of the nation.